2016
DOI: 10.1016/j.envpol.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Fate of engineered cerium oxide nanoparticles in an aquatic environment and their toxicity toward 14 ciliated protist species

Abstract: The potential environmental impacts of engineered cerium oxide nanoparticles (CeO2 NPs) on aquatic organisms have remained largely unknown. Therefore, the laboratory study featured herein was performed to determine the fate of CeO2 NPs in an aquatic environment and their toxicity towards 14 different ciliated protist species at a specified population level. An investigation of 48 h aggregation kinetics in the Dryl's solution showed the CeO2 NPs to be relatively stable. The pH values in three test medium were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Moreover, the acute toxicity of metal oxide NPs to Paramecium multimicronucleatum has shown that the 48-h LC 50 values of these NPs decreased as follows: Al 2 O 3 < TiO 2 < CeO 2 < ZnO < SiO 2 < CuO < Fe 2 O 3 NPs ( Figure 3 a), suggesting a positive correlation between the bonding strength of metal oxide NPs and the cell surface and the toxicity in unicellular organisms ( Figure 3 b,c) [ 212 ]. Furthermore, a recent study on the toxicity of CeO 2 NPs to 14 ciliated protist species showed that the CeO 2 NP adsorption on the protist surface rather than phylogenetical conservation induced the toxicity due to a negative correlation between LC 50 values and the surface-to-volume ratio of protists [ 213 ]. In addition, based on the chronic exposure to 1 and 5 mg·L −1 of TiO 2 NPs for 21 days, severe growth retardation, mortality and reproductive capacity reduction were all observed in D. magna .…”
Section: Environmental Impacts Of Metal-based Nps On Aquatic Organmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the acute toxicity of metal oxide NPs to Paramecium multimicronucleatum has shown that the 48-h LC 50 values of these NPs decreased as follows: Al 2 O 3 < TiO 2 < CeO 2 < ZnO < SiO 2 < CuO < Fe 2 O 3 NPs ( Figure 3 a), suggesting a positive correlation between the bonding strength of metal oxide NPs and the cell surface and the toxicity in unicellular organisms ( Figure 3 b,c) [ 212 ]. Furthermore, a recent study on the toxicity of CeO 2 NPs to 14 ciliated protist species showed that the CeO 2 NP adsorption on the protist surface rather than phylogenetical conservation induced the toxicity due to a negative correlation between LC 50 values and the surface-to-volume ratio of protists [ 213 ]. In addition, based on the chronic exposure to 1 and 5 mg·L −1 of TiO 2 NPs for 21 days, severe growth retardation, mortality and reproductive capacity reduction were all observed in D. magna .…”
Section: Environmental Impacts Of Metal-based Nps On Aquatic Organmentioning
confidence: 99%
“… Surface interactions affect the toxicity of metal oxide NPs toward Paramecium : ( a ) survival ratios of P. multimicronucleatum after 48 h of exposure to NPs; ( b ) net interaction energy profiles between NPs and P. multimicronucleatum ; ( c ) relationship of the magnitude of energy barrier and the 48-h LC 50 of metal oxide NPs to P. multimicronucleatum (reproduced with permission from [ 213 ], Copyright American Chemical Society, 2012) …”
Section: Figurementioning
confidence: 99%
“…27 The size and surface modifications of CeO 2 NPs obviously influenced the temporal partition behavior of nanoparticles in aquatic systems and their bioavailability and toxicity to the biota species. 22,23,25 Nevertheless, previous studies on food chains containing no more than three species could not fully represent the situation of a complete ecosystem or mimic the real environmental scenario. It was thus of importance to study the long-term effect of CeO 2 NP exposure in a water ecosystem constituted by multiple abiotic and biotic components to clarify their environmental fate and potential impacts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…27 The size and surface modifications of CeO 2 NPs obviously influenced the temporal partition behavior of nanoparticles in aquatic systems and their bioavailability and toxicity to the biota species. 22,23,25 Nevertheless, previous studies on food chains containing no more than three species could not fully represent the situation of a complete ecosystem or mimic the real environmental scenario.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) are unparalleled compounds due to their tiny size ( than 100 nm), and size-dependent characteristics (length, width, height, volume, and mass) (Zhang et al, 2016). Currently, the production of engineered NPs, especially metal oxide nanomaterials (NMs) were extensively increased due to the numerous and widely used commercial applications worldwide.…”
Section: Introductionmentioning
confidence: 99%